Stigma in the context of schools: analysis of the phenomenon of stigma in a population of university students. Issue 1 (December 2016) - Pingani, Luca; Catellani, Sara; Del Vecchio, Valeria; Sampogna, Gaia; Ellefson, Sarah; Rigatelli, Marco; Fiorillo, Andrea; Evans-Lacko, Sara; Corrigan, Patrick
Abstract Background Students have stereotyped views about people with mental illness. In particular, they believe that these persons are incurable, dangerous, unpredictable and responsible for their condition. This study aims to investigate the levels of public stigma in an Italian university population. Methods The Attribution Questionnaire 27 - Italian Version (AQ-27-I) was administered to a sample of students from the Faculty of Medicine and Surgery of the University of Modena and Reggio Emilia. After examining the psychometric characteristics of the AQ-27-I (Cronbach's Alpha and Confirmatory Factor Analysis), multiple linear regression analyses were carried out to identify the predictors of stigmatizing attitudes in this population. Results Three hundred and eleven students completed the questionnaire, with a response rate of 32.81 % (out of the 948 contacted by email). The AQ-27-I showed good psychometric properties with an α = .68, and the fit indices of the models that partially supported the factor structure and paths. The two variables identified as possible predictors of stigmatizing attitudes (total score of AQ-27-I) were age and time spent reading newspapers. Conclusions Antistigma campaigns are needed in university contexts, targeted in particular to students in health professions.